PEMANFAATAN POT RAMAH LINGKUNGAN BERBASIS GEOPOLIMER SEBAGAI WUJUD GERAKAN MENUJU NET ZERO EMISSION 2060 - Iqlima Nuril Amini; Meity Wulandari; Irfan Prasetyo Loekito; Arie Wardhono; Muhammad Imaduddin (Jurnal Abdi Masyarakat, 2026)
The implementation of environmentally sustainable materials plays a crucial role in reducing carbon emissions in the construction sector. This activity aimed to enhance community understanding of geopolymer materials through outreach and hands-on demonstrations of geopolymer pot production in Tanggumong Village, Sampang District. Geopolymer was chosen as an alternative to conventional cement due to its ability to utilize industrial byproducts such as fly ash. The program included material presentations, interactive discussions, and practical demonstrations. Evaluation results showed an increase in participants’ average understanding from 55% to 81%. Specifically, basic knowledge improved from 49% to 81%, attitudes from 85% to 94%, and practical skills from 85% to 88%. The community responded positively to the geopolymer pot as an environmentally friendly alternative material. Overall, this activity effectively enhanced environmental literacy and awareness of sustainable material use while contributing to the achievement of SDG 12 and SDG 13.